2010
DOI: 10.1098/rspb.2009.2086
|View full text |Cite
|
Sign up to set email alerts
|

Species interactions–area relationships: biological invasions and network structure in relation to island area

Abstract: The relationship between species number and island area is a fundamental rule in ecology. However, the extent to which interactions with exotic species and how the structure of species interactions is related to island area remain unexplored. Here, I document the relationship between island area and (i) interactions with exotic species and (ii) network structure of species interactions in the context of mutualistic interactions between ants and extrafloral nectary-bearing plants on the oceanic Ogasawara (Bonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 51 publications
(101 reference statements)
6
63
3
Order By: Relevance
“…The endemic ant, Camponotus ogasawarensis, has been observed escaping from the introduced ant, Pristomyrmex punctatus, on native plants (Sugiura 2010b). When introduced P. punctatus worker ants were experimentally excluded from native plants, C. ogasawarensis visited the extrafloral nectaries immediately after the exclusion (Sugiura 2010b).…”
Section: Interspecific Competitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endemic ant, Camponotus ogasawarensis, has been observed escaping from the introduced ant, Pristomyrmex punctatus, on native plants (Sugiura 2010b). When introduced P. punctatus worker ants were experimentally excluded from native plants, C. ogasawarensis visited the extrafloral nectaries immediately after the exclusion (Sugiura 2010b).…”
Section: Interspecific Competitionmentioning
confidence: 99%
“…When introduced P. punctatus worker ants were experimentally excluded from native plants, C. ogasawarensis visited the extrafloral nectaries immediately after the exclusion (Sugiura 2010b). Therefore, native ants may suffer from interference or exploitative competition with introduced ants.…”
Section: Interspecific Competitionmentioning
confidence: 99%
“…Sugiura [69] examined interactions of both native and exotic plants and ants on Japanese islands and found that the number of interactions increased significantly with increasing island area when all species were considered. However, network connectance (the proportion of possible interactions between species that are realized) and nestedness (a proxy of asymmetric specialization, where generalists interact with each other and specialists interact only with generalists) both decreased with island area [69]. Similar results were observed in a meta-analysis of plant-pollinator networks, where increasing study area size (i.e., habitat amount) positively correlated with the number of interactions, but negatively correlated with nestedness [70].…”
Section: Patch Size and Habitat Amountmentioning
confidence: 99%
“…Although there is an increasing interdisciplinary application of networks in epidemiology, relatively little attention has been paid to these analytical approaches in plant sciences. Hence the need for this review, which aims to summarize recent progress in this rapidly developing field and to highlight research challenges specific to plant pathology.In today's plant pathology, as in other fields, there is a need for integrating investigations at the molecular, mycelium, plant, regional and international scale (9,48,102,111,118,120,132). Networks can provide such a unifying framework.…”
mentioning
confidence: 99%
“…In today's plant pathology, as in other fields, there is a need for integrating investigations at the molecular, mycelium, plant, regional and international scale (9,48,102,111,118,120,132). Networks can provide such a unifying framework.…”
mentioning
confidence: 99%